Kualitas Kualitas Fisik Daging Sapi Yang Dijual Di Pasar Tradisional Kutoarjo Kabupaten Purworejo. Indonesia: Physical Quality Of Beef Sold In Kutoarjo Traditional Market, Purworejo Regency. Indonesia (Jurnal Riset Agribisnis dan Peternakan, 2025)
Beef sold in traditional markets needs to be considered for quality to maintain food safety for consumers. The purpose of this study is to determine the physical quality of beef sold in Kutoarjo Traditional Market, Purworejo Regency. The method used in this study is descriptive, taking samples from 12 beef traders in the market. The variables observed were the water content, pH, cooking loss, and meat color. The data obtained were statistically analyzed by testing the mean values and then presented descriptively in the form of tables and diagrams. The results showed that the average water content of the beef was 73.31%, which is still within normal limits. The average pH value of the beef was 5.39, with most traders showing pH values classified as normal. The cooking loss of the beef averaged 37.02%, which also falls within the normal range. Additionally, the average color scale of the beef reached 5.22, of beef reaches 5.22, indicating that the meat is still fresh and of good quality. The conclusion indicates that the physical quality of beef sold at Kutoarjo Traditional Market mostly still meets normal standards.
Keywords: Physical quality; Beef; Traditional Market; Purworejo Regency